Midcareer Faculty Needs Identified by the Midwest Nursing Research Society Midcareer Scholars Task Force. (May 2019) - Hershberger, Patricia E.; Minton, Mary; Voss, Joachim G.; McCarthy, Ann Marie; Murrock, Carolyn J.; Topp, Robert; Talsma, AkkeNeel
The midcareer academic period is largely unexplored despite its lengthy duration and challenging career expectations at academic institutions. The Midwest Nursing Research Society (MNRS) formed a Midcareer Scholars Task Force to address this gap. All active members of MNRS were invited to participate in a cross-sectional survey, of which 286 members completed. The most frequently perceived institutional support for midcareer scholars was for conference attendance followed by librarian assistance. Most assistant and associate professors perceived mentoring as a critical MNRS organizational activity to advance their research and careers; however, full professors saw MNRS's responsibility in mentoring midcareer scholars differently. Existing academic institutions were perceived as limited in their support and success in midcareer scholar mentorship efforts. There are considerable needs for midcareer scholar support and mentoring, and professional organizations can play an important role to fill this gap. Targeted mentoring and professional development initiatives are needed to better support midcareer faculty.